Biochemical assessment of in vitro and in vivo culture of Tylophora indica (Burm. F.) Merr - Kaushik, Antaryami; Gurnani, Chandra; Sunder, Shyam; Dhingra, Abha; Chimpa, Vikram (Kathmandu University Journal of Science Engineering and Technology, 2010)
Tylophora indica (Burm. F.) Merr is an endangered plant which can be protected from extinction by its large scale production. Nodal segments of healthy plants are used as explants and cultured on MS Basal medium fortified with different growth regulators. Optimum shoot induction conditions from explants were established. In vitro and in vivo phytochemical test were done by using standard methods for chlorophyll, carbohydrates, proteins, lipids and starch. 3mg/l 2, 4 D showed maximum and success full callus production. Shoot initiation started in 7 days and best shoot regeneration reported with 3 mg/ml BAP in Basal medium. Combination of IBA and NAA in concentration 2 and 4 mg/l respectively proved to be best for root initiation. Concentration of chlorophyll, protein, lipid, carbohydrate, and starch in vitro and in vivo culture are investigated.